1998
DOI: 10.1042/cs0940255
|View full text |Cite
|
Sign up to set email alerts
|

Skin Microcirculation in Patients with Type I Diabetes with and without Neuropathy after Neurovascular Stimulation

Abstract: 1. Neurovascular inflammation is impaired in patients suffering from diabetic neuropathy. The aim of our study was to evaluate the distribution of nutritive and total skin blood flow in diabetic patients with and without neuropathy after neurovascular stimulation with acetylcholine. 2. Twenty patients with Type I diabetes, 10 with and 10 without neuropathy, and 10 age-matched non-diabetic control subjects, underwent microvascular investigations before and after neurovascular stimulation by intracutaneous appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 18 publications
(12 reference statements)
0
19
0
Order By: Relevance
“…The iontophoresis of deionized water in the same polarity with that of acetylcholine (i.e., with an anodal constant current) has been previously shown to lead to a small nonspecific galvanic effect (20,21). In contrast, iontophoresis with a cathodal current, as used for the iontophoresis of sodium nitroprusside, has been reported in one study to result in a significant nonspecific vasodilatory response (22).…”
Section: Foot Levelmentioning
confidence: 86%
See 1 more Smart Citation
“…The iontophoresis of deionized water in the same polarity with that of acetylcholine (i.e., with an anodal constant current) has been previously shown to lead to a small nonspecific galvanic effect (20,21). In contrast, iontophoresis with a cathodal current, as used for the iontophoresis of sodium nitroprusside, has been reported in one study to result in a significant nonspecific vasodilatory response (22).…”
Section: Foot Levelmentioning
confidence: 86%
“…However, the magnitude of the contribution of each of these two factors to the total vasodilation has not been adequately studied, and the currently available data are conflicting. Thus, although some studies have suggested a considerably higher contribution of the neurovascular response, the techniques used did not allow the precise quantification of this contribution (8,21). On the other hand, another study has shown that local sensory inhibition by topical application of lignocaine and prilocaine did not have an effect on the total vasodilatory response to the iontophoresis of acetylcholine (22).…”
Section: Foot Levelmentioning
confidence: 98%
“…This possibility was suggested by Forst et al (22), who proposed that the effect of intracutanous ACh on CuBF is mediated mainly by the axon reflex. The situation is more complex, however, as there is evidence that the iontophoretic current alone may also induce an axon reflex (9).…”
mentioning
confidence: 88%
“…Before the start of the investigation, the patients rested in a supine position for at least 15 min and the mean LDF was recorded for 3 min at a probe temperature of 37°C and 44°C. The mean individual coefficient of variation of microvascular blood flow measurement using this method is 20% (8,9).…”
Section: Laser Doppler Fluxmetrymentioning
confidence: 98%